FOREIGN EXPERIENCE IN THE FIELD OF ACTIVITY OF QUASI-PUBLIC SECTOR - Asyl Zhaksylykovich, Садыков (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
In this article the author considers the international experience in the sphere of quasi-public sector activity, namely the scope of the public-private partners hip in foreign countries, methods of evaluation of the public-private partners hip projects, the principles of the public sector formation.